Use of thermally activated Fenton sludge for Cd removal in zinc smelter wastewater: Mechanism and feasibility of Cd removal - Cho, Eun Ji; Kang, Jin Kyu; Lee, Chang Gu; Bae, Sungjun; Park, Seong Jik (Environmental Pollution, 2023)
Fenton sludge is a byproduct of the Fenton process that contains large amounts of Fe and Ca. Because of the secondary contamination generated during the disposal of this byproduct, ecofriendly treatment methods are needed. In this study, we used Fenton sludge to remove the Cd discharged from a zinc smelter factory, using thermal activation to enhance the Cd adsorption capacity. Among the various temperatures considered (300–900 °C), the Fenton sludge that was thermally activated at 900 °C (TA–FS–900) adsorbed the highest amount of Cd because of its high specific surface area and high Fe content. Cd was adsorbed onto TA–FS–900 via complexation with C–OH, C–COOH, FeO−, and FeOH and cation exchange with Ca2+. The maximum adsorption of TA–FS–900 was 260.2 mg/g, indicating that TA–FS–900 is an efficient adsorbent, comparable to those reported in the literature. The initial Cd concentration in the zinc smelter wastewater discharged was 105.7 mg/L, 98.4% of which was removed by applying TA–FS–900, suggesting the applicability of TA–FS–900 for real wastewater containing high concentrations of various cations and anions. The leaching of heavy metals from TA–FS–900 was within the EPA standard limits. We concluded that the environmental impact of Fenton sludge disposal can be reduced, and the use of Fenton sludge can add value to the treatment of industrial wastewater in terms of the circular economy and environment.
Keywords: Cd adsorptions; Cd removal; Eco-friendly; Fenton sludge; Fenton's process; Large amounts; Thermal activation; Thermally activated; Treatment methods; Zinc smelter wastewater; Adsorption; Cadmium; Feasibility Studies; Sewage; Waste Disposal, Fluid; Wastewater; Water Pollutants, Chemical; Zinc; Adsorption; Cd removal; Fenton sludge; Thermal activation; Zinc smelter wastewater